38.9k views
1 vote
Equivalent expression for 12a+6b

2 Answers

4 votes
Simplifying 12a + 6b = 0 Solving 12a + 6b = 0 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-6b' to each side of the equation. 12a + 6b + -6b = 0 + -6b Combine like terms: 6b + -6b = 0 12a + 0 = 0 + -6b 12a = 0 + -6b Remove the zero: 12a = -6b Divide each side by '12'. a = -0.5b Simplifying a = -0.5b
User Agathe
by
5.9k points
2 votes
The answer is 6(2a+b)
To get the equivalent expression you would have to simplify it.
User Justinkmunger
by
5.5k points